Utilizing NPKS fertilizer for the enhancement of Pennisetum purpureum growth and phytoremediation of arsenic in treatment wetland - Rahman, Md Ekhlasur; Uddin, Md Kamal; Shamsuzzaman, S. M.; Mahmud, Khairil; Abd Shukor, Mohd Yunus; Abd Ghani, Siti Salwa; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Akter, Amaily; Halmi, Mohd Izuan Effendi (Taylor and Francis, 2025)
Phytoremediation of arsenic in constructed wetlands (CWs) is becoming the most efficient, eco-friendly, and sustainable technology worldwide. This research aimed to explore the impact of utilizing NPKS fertilizer on the enrichment of Pennisetum purpureum growth and phytoremediation of arsenic in CWs. The study comprised control and 2 phytoremediation treatments with P. purpureum plants: 39 mg kg−1As alone and the application of 0.04% NPKS fertilizer with 39 mg kg−1As. This experiment was carried out in CWs for 42 days. Bioavailable and total As were determined by ICP-OES. P. purpureum developed effectively in the phytoremediation treatment with 0.04% NPKS fertilizer application till the end of the experiment. The arsenic phytoremediation treatment with 0.04% NPKS fertilizer removed 72.54% bioavailable arsenic, 72.52% total arsenic, and 0.05% arsenic in the leachate of CWs. The fresh weight of P. purpureum rose considerably when treated with 0.04% NPKS fertilizer in comparison to the arsenic-alone treatment. The maximum efficiency of arsenic absorption at 42 days attained 5041.7 ± 120.4 mg kg−1 DW in the phytoremediation treatment with 0.04% NPKS fertilizer application. These results suggest that phytoremediation treatments with 0.04% NPKS fertilizer can be used in As phytoremediation in anthropogenically polluted environments due to its high capability to uptake As.